Multiscale reconstruction of various vessels in the intact murine liver lobe - Qi Zhang; Anan Li; Siqi Chen; Jing Yuan; Tao Jiang; Xiangning Li; Qingming Luo; Zhao Feng; Hui Gong (Communications Biology, 2022)
High-definition fluorescent micro-optical sectioning tomography is employed to resolve fine structures of multiple vessel types in the intact liver.